2016
DOI: 10.1111/resp.12872
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and extra‐terminal protein mimic JQ1 decreases inflammation in human vascular endothelial cells: Implications for pulmonary arterial hypertension

Abstract: Background and objectiveNuclear factor kappa B (NF‐kB)‐mediated inflammatory gene expression and vascular endothelial cell proliferation/remodelling are implicated in the pathophysiology of the fatal disease, pulmonary arterial hypertension (PAH). Bromodomain and extra‐terminal (BET) proteins are essential for the expression of a subset of NF‐kB‐induced inflammatory genes. BET mimics including JQ1+ prevent binding of BETs to acetylated histones and down‐regulate the expression of selected genes.MethodsThe effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…44,45 When activated by inflammation or other stimuli, endothelial cells may become dysfunctional and can alter the underlying SMCs by releasing inflammatory cytokines. 45 Interestingly, a recent article by Mumby et al 46 established the implication of BRD4 in triggering the expression of inflammatory genes (IL-6 and IL-8) in human pulmonary microvascular endothelial cells. Also, a recent study suggested that BRD4 plays a role in the atherogenic processes by regulating an inflammatory response in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 When activated by inflammation or other stimuli, endothelial cells may become dysfunctional and can alter the underlying SMCs by releasing inflammatory cytokines. 45 Interestingly, a recent article by Mumby et al 46 established the implication of BRD4 in triggering the expression of inflammatory genes (IL-6 and IL-8) in human pulmonary microvascular endothelial cells. Also, a recent study suggested that BRD4 plays a role in the atherogenic processes by regulating an inflammatory response in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…JQ1 administration (50 mg/kg) reduced aortic plaque area by 40% in cholesterol fed Ldlr −/− mice [98]. It also suppressed p65 recruitment to the IL-6 and IL-8 promoters in human pulmonary microvascular endothelial cells (HPMEC) which inhibited their expression at both the mRNA and protein level [99].…”
Section: Bromodomain and Extra-terminal Domain Inhibitorsmentioning
confidence: 99%
“…Mumby et al . found that key enzymes integral in epigenetic regulation are dysfunctional in PAH patients . Furthermore, drugs targeting epigenetic pathways could inhibit inflammation and may therefore provide novel therapeutic options for this devastating condition.…”
Section: Pulmonary Vascular Diseasementioning
confidence: 99%